How important is computing technology for library and information science research? - Thelwall, Mike; Maflahi, Nabeil (Library & information science research, 2015)
Computers in library and information science (LIS) research have been an object of study or a tool for research for at least fifty years, but how central are computers to the discipline now? This research analyses the titles, abstracts, and keywords of forty years of articles in LIS-classified journals for trends related to computing technologies. The proportion of Scopus LIS articles mentioning some aspect of computing in their title, abstract, or keywords increased steadily from 1986 to 2000, then stabilised at about two thirds, indicating a continuing dominance of computers in most LIS research. Within this general trend, many computer-related terms have peaked and then declined in popularity. For example, the proportion of Scopus LIS article titles, abstracts, or keywords that included the terms “computer” or “computing” decreased fairly steadily from about 20% in 1975 to 5% in 2013, and the proportion explicitly mentioning the web peaked at 18% in 2002. Parallel analyses suggest that computing is substantially less important in two related disciplines: education and communication, and so it should be seen as a key aspect of the LIS identity. •Two-thirds of Scopus LIS articles mentioned an aspect of computing in their title, abstract, or keywords after 2000.•Scopus LIS article titles, abstracts, or keywords mentioning computer or computing decreased from 20% in 1975 to 5% in 2013.•Parallel analyses suggest that computing is much less important in two related disciplines: education and communication.•Computing should be recognized as a key aspect of the LIS identity.